Gamma-radiation Induced Degradation of the Electrical Characteristics of NMOSFETs - Ruangphait, Anucha; Kerdpradist, Amonrat; Muanghlua, Rangson; Wongprasert, Yothin (My University, 2022)
In this paper, we present the gamma-radiation induced degradation of the electrical characteristics of N-channel Metal Oxide Semiconductor Field Effect Transistors (NMOSFETs). The exposure was done with a60Co gamma-ray source over the total dose range of 1 kGy to 10 kGy, with a dose rate of 3.9 kGyhr. The effects of irradiation induced degradation on device parameters such as threshold voltage, low field mobility, device transconductance (Gm), saturation drain current, off state leakage current and subthreshold swing were investigated. The threshold voltage was determined using the linear extrapolation method. The device dimensions with Wide/ Long channel that excluded the Narrow Channel Effect (NCE) and the Short Channel Effect (SCE) were measured. The results showed that the threshold voltage, device transconductance and low field mobility decreased but the saturation drain current, off state leakage current and subthreshold swing increased as the gamma irradiation increased. Finally, the macro parameter models were investigated and discussed.
Keywords: device parameters; gamma radiation; NMOSFETs; threshold voltage